2019
DOI: 10.1007/s10048-019-00587-0
|View full text |Cite
|
Sign up to set email alerts
|

Nervous NDRGs: the N-myc downstream–regulated gene family in the central and peripheral nervous system

Abstract: The N-Myc downstream-regulated gene (NDRG) family consists of four members (NDRG1, NDRG2, NDRG3, NDRG4) that are differentially expressed in various organs and function in important processes, like cell proliferation and differentiation. In the last couple of decades, interest in this family has risen due to its connection with several disorders of the nervous system including Charcot-Marie-Tooth disease and dementia, as well as nervous system cancers. By combining a literature review with in silico data analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 91 publications
1
27
0
Order By: Relevance
“…When investigating gene functions, we observed that twelve out of the top twenty (60.0%) genes were related to the nervous system based on their gene ontologies (Additional file 1 : Table S3), resembling the previously identified neuronal-specific expression of NDRG4 [ 27 29 ].…”
Section: Resultssupporting
confidence: 68%
“…When investigating gene functions, we observed that twelve out of the top twenty (60.0%) genes were related to the nervous system based on their gene ontologies (Additional file 1 : Table S3), resembling the previously identified neuronal-specific expression of NDRG4 [ 27 29 ].…”
Section: Resultssupporting
confidence: 68%
“…NDRG1 was highly expressed in GB but not in LGG clinical samples compared to normal brain tissue ( Figure 8 A and Figure S6 ). NDRG1 is a multifaceted protein that has been shown to regulate nerve myelination, stress response, lipid biosynthesis and metabolism, exocytosis and differentiation [ 64 ]. NDRG1 has been shown to confer resistance to temozolomide, via binding and stabilization of MGMT [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…The role of NDRG4 in human cancers is quite controversial, in particular in tumors of the central nervous system [ 39 ]. In fact, NDRG4 is upregulated in tumors of central nerve system, such as glioblastoma [ 28 ] and meningioma [ 40 ], functioning as an oncogene.…”
Section: Discussionmentioning
confidence: 99%